2018
DOI: 10.3389/fimmu.2018.02241
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1+ Regulatory B Cells Are Significantly Decreased in Rheumatoid Arthritis Patients and Increase After Successful Treatment

Abstract: Background: B cells play an important role in the development and maintenance of rheumatoid arthritis (RA). Although IL-10–producing B cells represent a major subset of regulatory B cells (Bregs) able to suppress autoimmune and inflammatory responses, recent reports showed that B cell-mediated immune suppression may also occur independent of IL-10. For instance, B cells can modulate T cell immune responses through the expression of regulatory molecules such as PD-L1. So far, PD-L1-expressing B cells have not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 48 publications
3
46
1
1
Order By: Relevance
“…Comparing with the HCs, it has been reported that invasive breast cancer patients had significantly increased quantity of PD‐L1 + Bregs, which possibly related to the immune escape . Similarly in rheumatoid arthritis patients, the amount of PD‐L1 + Bregs increased significantly after treatment . In our study, we confirmed that AR patients had less PD‐L1 + Bregs.…”
Section: Discussionsupporting
confidence: 82%
“…Comparing with the HCs, it has been reported that invasive breast cancer patients had significantly increased quantity of PD‐L1 + Bregs, which possibly related to the immune escape . Similarly in rheumatoid arthritis patients, the amount of PD‐L1 + Bregs increased significantly after treatment . In our study, we confirmed that AR patients had less PD‐L1 + Bregs.…”
Section: Discussionsupporting
confidence: 82%
“…However, other findings suggest instead that CD38 can also play regulatory roles in RA. For instance, reduced CD38 hi PDL1 + CD24 hi circulating regulatory transitional B cells have been reported in RA patients (129). In summary, many CD38 + pathogenic populations appear to increase during RA.…”
Section: Rheumatoid Arthritismentioning
confidence: 96%
“…Relevant intrinsic factors include changes in major histocompatibility complex (MHC) class II [55], BCR signaling responses [56][57][58], and TLR responses [59,60]. These factors in addition to deficient Breg cells [61,62] and abnormal of extrafollicular germinal centers (GC) formation [6,63] result in alterations to B cell subsets highly connected to autoreactive ASCs (Figure 2). [64].…”
Section: Relevant Extrinsic and Intrinsic Factors Sustainmentioning
confidence: 99%